2017
DOI: 10.1101/189100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrative genomics analysis identifiesACVR1Bas a candidate causal gene of emphysema distribution in non-alpha 1-antitrypsin deficient smokers

Abstract: Background: Several genetic risk loci associated with emphysema apico-basal distribution

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…We also performed functional evaluation and demonstrated allelespecific enhancer activity for an emphysema distribution-associated variant that alters the lung expression of ACVR1B (activin A receptor type 1B), an activin receptor in the transforming growth factor (TGF)-b signaling pathway. Some of these results were previously reported in the form of an abstract (13).…”
supporting
confidence: 55%
See 1 more Smart Citation
“…We also performed functional evaluation and demonstrated allelespecific enhancer activity for an emphysema distribution-associated variant that alters the lung expression of ACVR1B (activin A receptor type 1B), an activin receptor in the transforming growth factor (TGF)-b signaling pathway. Some of these results were previously reported in the form of an abstract (13).…”
supporting
confidence: 55%
“…We analyzed 11,532 non-alpha-1 antitrypsin-deficient current and former smokers with complete genotype and computed tomographic densitometry data from four cohorts: the COPDGene NHW (Genetic Epidemiology of COPD study non-Hispanic whites), COPDGene African Americans, the GenKOLS (Genetics of Chronic Obstructive Lung Disease), and the ECLIPSE (Evaluation of COPD Longitudinally to Identify Predictive Surrogate Endpoints) studies. Detailed descriptions, including study populations, genotyping quality control, and genotyping imputation, were published previously (12)(13)(14).…”
Section: Study Populationsmentioning
confidence: 99%
“…For example, multiple studies have suggested the TGFB pathway is associated with COPD (50), and the TGFB2 locus was associated with COPD in GWAS (51). Our study identified ACVR2B as a potential candidate; of interest, ACVR1B, an activin receptor which interacts with ACVR2B (52) was identified in a network-informed genetic association study of COPD (53) and in an integrative analysis of emphysema distribution (54).…”
Section: Discussionmentioning
confidence: 71%